Collaboration and Conflict: Multi-Disciplinary Teams Developing Multimedia for Preservice and Inservice Education - Linda P. Thurston (Educational Considerations, 1999)
Interactive multimedia is becoming a fixed feature in the delivery of instruction at all educational levels. The process of multimedia places the learning potential of technology in the hands of the learner and such features as screen design, interactivity, audio and video elements, and learner control and navigation are educationally effective.